IMPLIKASI PUTUSAN MAHKAMAH AGUNG NOMOR 46 P/HUM/2018 TERHADAP MANTAN NARAPIDANA DAPAT MENJADI CALON LEGISLATIF DALAM PENYELENGGARAAN GOOD GOVERNANCE - Inayah, Asti (MIH Unsoed, 2016)
This election is a representation of people's representatives who have goodqualifications and background so that through the role of independent institutions the KPU has the authority to make KPU Regulation Number 20 of 2018 concerning Nominations of Members of the House of Representatives (DPR), the Regional Representative Council (DPRD) of the Province, and Regency/City DPRD which limits the political rights of ex-convicts of corruption. The limitation of freedom to contribute to elections is contrary to the basic principles of the rule of law in Indonesia which upholds human rights which later gave birth to the Supreme Court Decision Number 46 P/HUM/2018 and has implications for the implementation of Good Governance in Indonesia.The approach method used in this research is normative juridical research. The sources of legal material contained in this study come from primary, secondary and tertiary legal materials with data collection techniques based on literature studies and data analysis techniques using deductive methods. Based on the results of this study that the legal considerations of judges in the MA Decision 46 P / HUM / 2018 that the Petitioner is a former convict of corruption and political rights have never been revoked due to the entry into force of Article 4 paragraph (3), Article 11 paragraph (1) letter d and Appendix Model B .3 PKPU Number 20 Year 2018 Concerning Nominations for Members of the House of Representatives, Provincial Regional House of Representatives and Regency/City People's Representative Council which becomes a necessity that legislative nominations come from clean figures and never have a track record of integrity flaws. The validity of the Supreme Court's Decree has implications for the implementation of good governance in the principle of participation, namely the people's involvement in the process of governing the government in an election even though a person is a former convict of corruption, as the resulting decisions have in common the concept of the rule of law and good governance in creating a perspective of Human Rights that is upheld high in the regulations as if implying that ex-convicts cannot be restricted in their political rights.